2007
DOI: 10.1002/jor.20442
|View full text |Cite
|
Sign up to set email alerts
|

Repair of porcine articular cartilage defect with a biphasic osteochondral composite

Abstract: Autologous chondrocyte implantation (ACI) has been recently used to treat cartilage defects. Partly because of the success of mosaicplasty, a procedure that involves the implantation of native osteochondral plugs, it is of potential significance to consider the application of ACI in the form of biphasic osteochondral composites. To test the clinical applicability of such composite construct, we repaired osteochondral defect with ACI at low cell-seeding density on a biphasic scaffold, and combined graft harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 59 publications
4
105
0
4
Order By: Relevance
“…294 Jiang et al investigated repair with a biphasic osteochondral composite consisting of b-tricalcium phosphate and dl-polylactide-co-glycolide seeded with autologous chondrocytes using single-stage surgery. 201 Commercially available composite implants have become available for the treatment of OCDs of the knee (TruFit Plug ® , Smith & Nephew, San Antonio, TX, USA). 452 Our research group is currently investigating the applicability of a novel resurfacing technique of the medial talar dome by means of a contoured metal implant (HemiCAP ® , Arthrosurface Inc., Franklin, MA, USA).…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…294 Jiang et al investigated repair with a biphasic osteochondral composite consisting of b-tricalcium phosphate and dl-polylactide-co-glycolide seeded with autologous chondrocytes using single-stage surgery. 201 Commercially available composite implants have become available for the treatment of OCDs of the knee (TruFit Plug ® , Smith & Nephew, San Antonio, TX, USA). 452 Our research group is currently investigating the applicability of a novel resurfacing technique of the medial talar dome by means of a contoured metal implant (HemiCAP ® , Arthrosurface Inc., Franklin, MA, USA).…”
Section: Future Developmentsmentioning
confidence: 99%
“…32,147,312 Therefore, experimental studies focus on improvement of these methods and development of alternativ es. 72,138,140,201,252,411,451 However, almost all studies investigate articular defects of the knee, while the ankle joint is rarely investigated. 81 These knee studies cannot reliably be extrapolated to patients with ankle defects, because biomechanical and biochemical properties of the knee and ankle are clearly different.…”
Section: Introductionmentioning
confidence: 99%
“…7 Most recent studies have demonstrated benefits of cell seeding on histological and mechanical properties of osteochondral reconstructions. 8,9 Other groups could not detect the mechanical superiority of cell-seeded constructs compared with empty scaffolds. 10 Irrespective of whether cells are used or not, reconstruction of the subchondral bone remains the key element to osteochondral reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…It was surprising to find the quality of repair tissue in our control group surpassed the thin layer of sparsely populated fibrous tissue, commonly found to occupy the osteochondral defects of large-animal models [14,25]. This was despite the use of skeletally mature animals, as germinal cells from the physis of skeletally immature animals [1] could contribute to cartilage regeneration.…”
Section: Discussionmentioning
confidence: 84%